Metaphorical Construction of Chinese Female Images in Media - Hong Xu (Дискурс, 2024)
Introduction. Media is closely related to discourse. Female metaphor in the media is not a simple reflection of the objective world, but a selective and conscious construction of female image in social reality. This study explores the metaphorical construction of Chinese female images in the blessings for women on “Women’s Day” through the media.Methodology and sources. While some words similar to the meanings of “Women’s Day” were selected as keywords, the researcher searched the Wechat platform for articles with the title including these keywords. Then, a total of 306 female metaphors were manually identified and selected as a corpus. With word frequency statistics of the corpus, this study sorted out the categories of Chinese female metaphors and analyzed female image constructed in the media.Results and discussion. It was found that the source domains of female metaphors mainly include plant, animal, daily object, fictional character, nature and environment. The female metaphors can be analyzed from the following categories: Woman is a Flower; Woman is Water; Woman is Half the Heaven; Woman is Light; Woman is a Fairy; Woman is a Book; Woman is a Tiger; Woman is a Jewel. Among them, “Woman is a Flower” is the most frequent one and dominates the female metaphors, while the beauty of “flowers” reflects the beauty of women, the blooming of “flowers” reflects the youth of women, and the aroma of “flowers” reflects the charming of women. “Woman is Water”, “Woman is Half of the Heaven”, “Woman is Light” are also frequent female metaphors, constructing the tenderness, high social status, unique charm and outstanding contribution of female. Other female metaphors also play a certain role in the construction of holiness, wisdom, independence, confidence, strength, precious character of female image. These metaphors construct diversified images in terms of the appearance, character, ability and value of women, and most of the women constructed are beautiful and gentle.Conclusion. It can be seen that the construction of female image in the media becomes diversified on the one hand, on the other hand it still follows the traditional thinking pattern. The paper suggests that gender discourse in the media has been diversified and improved, but still needs to strengthen the construction of equal female image in the harmonious society.